2021
DOI: 10.1186/s12885-021-08820-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of body-shape phenotypes with imaging measures of body composition in the UK Biobank cohort: relevance to colon cancer risk

Abstract: Background Body mass index (BMI), waist and hip circumference are strongly correlated and do not reflect body composition. A Body Shape Index (ABSI) and Hip Index (HI) define waist and hip size among individuals with the same weight and height and would thus reflect body density. We examined differences in body composition between body-shape phenotypes defined with ABSI and HI and used this information to propose explanations for associations between body-shape phenotypes and colon cancer risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 62 publications
(78 reference statements)
2
34
0
Order By: Relevance
“…The UK Biobank cohort includes half a million participants recruited between 2006 and 2010 from the general population of the United Kingdom (UK), at age 40–70 years 13 . Similar to our previous studies 3 , 11 , we have included in the current study only participants with self-reported white ancestry, because the number of participants with other ethnicities was relatively small. In total, we excluded 115,113 participants with missing measurements for testosterone and oestradiol, extreme or missing anthropometric measurements, mismatched genetic and self-reported sex, prevalent cancer at enrolment (defined as previously described 3 ), incident cancer or death within the first two years after enrolment (to minimise the influence of cancer cachexia), women pregnant at enrolment, participants receiving glucocorticoids or drugs influencing the production or action of sex steroids (listed in Supplementary Table S1 ), men receiving testosterone or 5α-reductase inhibitors and women with missing information for use of oral contraceptives or HRT.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The UK Biobank cohort includes half a million participants recruited between 2006 and 2010 from the general population of the United Kingdom (UK), at age 40–70 years 13 . Similar to our previous studies 3 , 11 , we have included in the current study only participants with self-reported white ancestry, because the number of participants with other ethnicities was relatively small. In total, we excluded 115,113 participants with missing measurements for testosterone and oestradiol, extreme or missing anthropometric measurements, mismatched genetic and self-reported sex, prevalent cancer at enrolment (defined as previously described 3 ), incident cancer or death within the first two years after enrolment (to minimise the influence of cancer cachexia), women pregnant at enrolment, participants receiving glucocorticoids or drugs influencing the production or action of sex steroids (listed in Supplementary Table S1 ), men receiving testosterone or 5α-reductase inhibitors and women with missing information for use of oral contraceptives or HRT.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated ABSI for both sexes with coefficients from NHANES 1999–2004 9 , but using waist circumference in mm and not in m as in the original formula, to derive ABSI values in the order of magnitude of waist circumference. We calculated HI for women with coefficients from NHANES III 10 , but HI for men with simple-fraction coefficients based on UK Biobank data 11 , to correct the underlying inverse correlation between HI calculated with the original coefficients and BMI observed in UK Biobank men 3 . …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the body mass index, which compares the body mass among individuals with the same height, ABSI and HI compare the waist and hip circumference, respectively, among individuals with the same body height and weight. Cardiometabolic risk factors and various cancers (including several cancers that are not obesity-related) have been positively associated with ABSI and negatively associated with HI [ 24 , 26 , 27 ]. Christakoudi et al [ 28 ] have also recently proposed to combine ABSI and HI to define four different body-shape phenotypes: (i) small-ABSI-small-HI individuals (“slim”); (ii) large-ABSI-large-HI individuals (“large”); (iii) large-ABSI-small-HI individuals (“apple”); (iv) small-ABSI-large-HI individuals (“pear”).…”
Section: Assessment Of Waist and Hip Circumferencesmentioning
confidence: 99%